2007
DOI: 10.1080/09638280600747793
|View full text |Cite
|
Sign up to set email alerts
|

Barriers against returning to work – as perceived by disability pensioners with back pain: A focus group based qualitative study

Abstract: Our study provides insight into the perceived barriers of returning to work and might be useful in future efforts aiming to help disability pensioners back to work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…Being off work or experiencing significant life changes (as are often brought about by injury or illness) can alter a person's psychological well-being, leading to problems such as stress, anxiety and depression, which can affect his or her ability to carry out aspects of the work [21,[25][26][27]. In addition to this, issues to do with confidence and motivation (such as worries about ability to return to the workplace, or perform in the job) are also reported to affect work-ability, especially in individuals who have been off work for longer than a few weeks [28,29].…”
Section: Body Structures and Body Functionsmentioning
confidence: 99%
“…Being off work or experiencing significant life changes (as are often brought about by injury or illness) can alter a person's psychological well-being, leading to problems such as stress, anxiety and depression, which can affect his or her ability to carry out aspects of the work [21,[25][26][27]. In addition to this, issues to do with confidence and motivation (such as worries about ability to return to the workplace, or perform in the job) are also reported to affect work-ability, especially in individuals who have been off work for longer than a few weeks [28,29].…”
Section: Body Structures and Body Functionsmentioning
confidence: 99%
“…7,8,22,27 The most severe outcome of this condition is permanent disability pension, which is hardly reverted. 20,21 According to two studies carried out in Norway, 14,15 the risk factors for disability pension and prognostic factors for back pain included being female; low education level and low socioeconomic condition; comorbidities; fatigue; and low professional qualifi cations.…”
Section: Introductionmentioning
confidence: 99%
“…In one (168), researchers found that people who had been off work for several years with back pain experienced negative effects on self-confidence and worried about their work ability. In addition, re-entry into work required special arrangements, for instance, environmental adjustments or reduced working hours (168). Two men and 15 women with musculoskeletal disorders who were on resting disability pensions and working part-time participated in a qualitative study about adaptation patterns in returning to work.…”
Section: Involvement In Future Occupational Life Activities: the Meanmentioning
confidence: 99%